A Virtual Laboratory Structure for Developing Programming Labs - Prieto-Blazquez, Josep; Herrera-Joancomarti, Jordi; Guerrero-Roldán, Ana-Elena (International Journal of Emerging Technologies in Learning (iJET), 2009)
Virtual Laboratories in a Virtual Learning Environment are indispensable spaces for developing practical activities. This paper proposes an integrated structure for Virtual Laboratories for undergraduate degree programmes in Computer Engineering and Software Engineering. The general structure proposed is based on the experience gained in designing and developing Virtual Laboratories during the past eleven years in a virtual university. Technological, pedagogical, strategic and academic staff resources are included in the Virtual Laboratories structure. The proposed structure has been applied to different computer areas and this paper presents the special case of a Virtual Programming Laboratory. Its effectiveness has been evaluated by the students using a web questionnaire.